2007
DOI: 10.1080/15700760601091200
|View full text |Cite
|
Sign up to set email alerts
|

Taking a Distributed Perspective to the School Principal's Workday

Abstract: Focusing on the school principal's day-to-day work, we examine who leads curriculum and instruction-and administration-related activities when the school principal is not leading but participating in the activity. We also explore the prevalence of coperformance of management and leadership activities in the school principal's workday. Looking across a range of administrationrelated and curriculum and instruction-related activities school principals participate in, we show that who takes responsibility for lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
165
0
22

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 11 publications
3
165
0
22
Order By: Relevance
“…The Vice-Chancellor contributes to institutional improvement by developing a collaborative team approach to school decision making process and problem solving. The administrator should employ a distributive approach to routine operations of the institution to ensure maximum involvement of other internal and external stakeholders (Spillane, Camburn & Pareja, 2007). Adopting a distributive approach involving other internal and external stakeholders in the management of affairs could enhance the efficiency and effectiveness of the decision making process of the institution for improved policy implementation and better learning outcomes of students.…”
Section: The Role Of Different Stakeholders In Improving Quality Univmentioning
confidence: 99%
“…The Vice-Chancellor contributes to institutional improvement by developing a collaborative team approach to school decision making process and problem solving. The administrator should employ a distributive approach to routine operations of the institution to ensure maximum involvement of other internal and external stakeholders (Spillane, Camburn & Pareja, 2007). Adopting a distributive approach involving other internal and external stakeholders in the management of affairs could enhance the efficiency and effectiveness of the decision making process of the institution for improved policy implementation and better learning outcomes of students.…”
Section: The Role Of Different Stakeholders In Improving Quality Univmentioning
confidence: 99%
“…The literature surveyed indicated that IL is a significant factor in facilitating, improving and promoting teachers' classroom instructional practices and the academic progress of students (Spillane, Camburn & Pareja, 2007;Pustejovsky, Spillane, Heaton & Lewis, 2009;Spillane & Zuberi, 2009). International empirical studies also affirm that IL plays a central role in shifting the emphasis of school-level activities more onto instructional improvements that lead to students learning better (Elmore, 2000;Spillane, Halverson & Diamond, 2000;Day, Harris, Hadfield, Tolley & Beresford, 2000;King, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though in no way undermining the role of the school principal, this recognition argues for thinking about leadership as something that potentially extends beyond those with formally designated leadership and management positions (Heller & Firestone, 1995;Ogawa & Bossert, 1995;Pitner, 1988;. Recent empirical work underscores the need for moving beyond an exclusive focus on formally designated leaders in studies of school leadership to identifying others who take responsibility for this work (Camburn, Rowan, & Taylor, 2003;Spillane, Camburn, & Pareja, 2007). Second, some scholars have called for attention to the practice of leadership in organizations as distinct from focusing exclusively on structures, roles, and positions (Eccles & Nohria, 1992;Gronn, 2003;Heifetz, 1994;Spillane, Halverson, & Diamond, 2004;Spillane & Diamond, 2007).…”
mentioning
confidence: 99%